On the Normative Function of Metatheoretical Endeavors - Zachary Stein (Integral Review, 2010)
I reconstruct an historical understanding of metatheory that emphasizes its normative function. The pioneering work of James Mark Baldwin inspires an account of how metatheoretical constructs emerge developmentally and come to serve a discourse-regulative function—overseeing, organizing, and regulating whole fields of discourse. Then I look to Charles S. Peirce as an exemplary normatively oriented metatheorist and explain how both continue a philosophical tradition concerned with the normative function of humanity more broadly. Thus, while I think it is valuable to pursue a variety of metatheoretical endeavors, including descriptive and empirical ones—mapping the terrain of various discourses, or summarizing their contributions—I argue for a specific vision of metatheory as a normative endeavor with rich intellectual and historical precedence. Unpacking some of the implications involved with this way of viewing and doing metatheory lead to considerations about the differences between two general types of metatheory (scholastic-reductionist and cosmopolitan-comprehensivist), the role of philosophical interlocutors in the public-sphere, and the trajectory of human evolution in the coming decades.